Polykria Milik Kita - Toekio, Soegeng (KEMADHA, 2012)
An exhibition is basically a work culture that implements a combination of creative and proficiency. The rate of development is determined by the offender, seeker, and the atmosphere of the times. When the cultural dynamics at the center of civilization, including what came to pass that mark the interaction dynamics of the movement known as hyperexogenous. The diversity of systems and the growing competition is very influential on cultural actors. Like a vortex of endless, global culture must be faced with an optimistic attitude. But beside that, there is negligence on the toughness of their own culture. In this fast-paced atmosphere of a gap there was a group of young people who dared to display works with the image of different traditions. Serving them is the answer to the advantage of local cultural (ethnic culture). Academic base that is grounded in local culture is essential for the existence of cultural capital of the nation. This exposure is only a fraction of the phenomenon of cultural work. Hopefully their enthusiasm will motivate other young people